KoPer: School Lıteracy Movement Strategy To Strengthen Readıng And Wrıtıng Skılls - Susi Lestari, Susi; Anam Sutopo; Fitri Puji Rahmawati (Elementary Teacher Education Program, Majalengka University, 2024)
The School Literacy Movement is an activity program that focuses on reading and writing skills. The School Literacy Movement was formed due to the low interest in reading and writing of students. So that the purpose of this school literacy movement is to achieve maximum quality of education quality related to reading and writing skills. The School Literacy Movement is a very important thing to develop through a strategy, namely KoPer (Literacy Group). KoPer (Literacy Group) has the purpose of strengthening reading and writing skills. This study aims to strengthen students' reading and writing skills through the school literacy movement strategy at Gonilan 02 State Elementary School, namely with KoPer (Literacy Group). The methods used in this research are observation, interview and documentation methods with the subjects of students, class teachers and the principal of Gonilan 02 State Elementary School. The results of this study are that there are three stages in the school literacy movement; the habituation stage, the learning stage and the development stage. Of the three stages, Gonilan 02 State Elementary School has implemented well through 15-minute reading activities, guided reading, shared reading, organizing a literacy-rich environment, compiling and making schedules, library visits, wall magazines and reading corners in class. In this KoPer (Literacy Group) there are strategies implemented by the school, namely, Digit Literacy, Library, Around the Region, and Literacy-Based Environments. This shows that KoPer(Literacy Group) is an alternative way to strengthen reading and writing skills for primary school students reading and writing skills for primary school students.